Experimental Study and Identification of a Dynamic ‎Deformation Model of Dry Clay at Strain Rates up to 2500 s-1‎ - Аleksandr Коnstantinov; Anatoly Bragov; Leonid Igumnov; Victor Eremeyev; Vladimir Balandin; Vladimir Balandin (Journal of Applied and Computational Mechanics, 2022)
The paper presents the results of an experimental study and numerical simulation of dynamic deformation of dry clay at strain rates of ~103 s-1. The main physical and mechanical characteristics of the clay were determined using the modified Split Hopkinson Pressure Bar method for testing of lowly cohesive media in a rigid cage. Three series of experiments were carried out at strain rates of 1400 s-1, 1800 s-1 and 2500 s-1. The maximum values of the realized in the experiment axial stresses in clay were about 400 MPa and maximum pressures were 250 MPa. Based on the results of the experiments, the dependences of axial stresses on axial deformations σx-εx, shear stresses on pressure τ-P and pressure on volumetric deformation P-e (curves of volumetric compressibility) were plotted. The shear resistance of clay is noted to be well described by the Mohr-Coulomb law. The obtained deformation diagrams are found to be practically independent of deformation rate. The clay behavior under dynamic loads is shown to be essentially nonlinear. On the basis of the obtained experimental data, a parametric identification of the clay deformation model in the form of Grigoryan's constitutive relation was carried out, which was implemented in the framework of the LS-DYNA software in the form of MAT_SOIL_AND_FOAM model. Using the LS-DYNA computational complex, a numerical simulation of the deformation process of a sample under real experimental conditions was carried out. In the computational experiment, the clay behavior was described by the identified model. Good agreement was obtained between numerical and experimental results.